2023
DOI: 10.46827/ejpe.v10i2.5000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two 8-Week Physical Training Models (Traditional and Specific) on Improved Military Physical Performance

Leandra Cristina Benetti Campos,
Fabio Angioluci Diniz Campos,
Emerson Franchini
et al.

Abstract: The aim of this study was to compare the effect of eight weeks of traditional physical training (TPT) and military-specific physical training (MSPT) on the physical and operational performance of infantry cadets of the Brazilian Air Force (BAF). This study consisted of 27 male cadets (22.8±1.6 years, 76.0±9.2 kg, 1.77±0.05 m) stratified according to initial levels of physical fitness and randomly allocated in TPT (n= 13) or MSPT (n= 14) groups. The TPT group performed the basic military physical training provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…However, to the researchers, this was the first study to determine the effects of Saudi Arabia's IMTC on body composition, physical fitness, and self-reported physical activity levels. The investigators observed a significant decrease in WC, which is consistent with previous studies in the literature [ 1 , 19 ]. WC is a crucial marker for identifying MetS risk, and the optimal cutoff values vary greatly depending on ethnicity [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, to the researchers, this was the first study to determine the effects of Saudi Arabia's IMTC on body composition, physical fitness, and self-reported physical activity levels. The investigators observed a significant decrease in WC, which is consistent with previous studies in the literature [ 1 , 19 ]. WC is a crucial marker for identifying MetS risk, and the optimal cutoff values vary greatly depending on ethnicity [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, LBM decreased unfavorably, which could be attributed to the duration of the study. Prior literature has shown increased LBM in studies that lasted ≥12 weeks [ 1 , 19 ]. It should be noted that even though some studies [ 1 , 19 ] have comparable training components to our research, the percentage of endurance/aerobic training was practically half of ours (40% compared to 80%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuerza resistencia abdominal. La prueba de abdominales se ejecutó considerando las recomendaciones de un estudio previo realizado en militares (Campos et al, 2017). El participante durante 1 minuto en una colchoneta, se ubica decúbito supino con las piernas flexionadas en 90°, los pies se separados y las manos detrás de la cabeza, una persona le afirmaba los pies mientras el ejecutante realizaba la prueba.…”
Section: Composición Corporalunclassified